Management of Native Soil Nitrogen for Reducing Nitrous Oxide Emissions and Higher Rice Production - Pandey, Keshav R.; Shah, S. C.; Becker, M. (Journal of Agriculture and Environment, 2009)
Present production of rice is far below its reported potential yield because of being Ndeficiency, the major constraint. Because of poverty, small farmers have to rely on native soil N-supply. Between wheat harvest and rice transplanting, a dry-to-wet season transition (DWT) period exist with changing soil moisture from aerobic to anaerobic and a large amount of native soil N loss is hypothesized. To study soil N dynamism and possible management options for DWT, two years field experiments were conducted in Chitwan with four land management treatments like bare fallow, mucuna, mungbean and maize. Treatments were randomly allotted in 10 m2 plots. During DWT, building up of 50-75 kg of nitrate-N was observed at 60-75 % field capacity (FC) soil moisture but lost after flooding through leaching and denitrification, resulting in low grain yield and N uptake of succeeding rice. Growing cover crops during DWT, reduced leaching loss by half and N2O emissions by two thirds of those in the bare fallows. Atmospheric-N addition by legumes ranged from 27 to 56 kg ha-1 depending on the types of legumes and increased N uptake and grain yield by 24-42 kg N ha-1 yr-1 and 1.2-2.1 Mg ha-1 yr-1respectively. Thus, cultivation of grain/green manure legumes appears economically and ecologically beneficial. Key Words: bare fallow, crop N uptake, denitrification, green manure, leaching, nitrate catch crops, nitrification The Journal of Agriculture and Environment Vol:9, Jun.2008 Page: 1-9